2017
DOI: 10.1016/j.autneu.2016.12.004
|View full text |Cite
|
Sign up to set email alerts
|

Profiling subjective symptoms and autonomic changes associated with cybersickness

Abstract: Our aim was to expand knowledge of cybersickness - a subtype of motion sickness provoked by immersion into a moving computer-generated virtual reality. Fourteen healthy subjects experienced a 15-min rollercoaster ride presented via a head-mounted display (Oculus Rift), for 3 consecutive days. Heart rate, respiration, finger and forehead skin conductance were measured during the experiment; this was complemented by a subjective nausea rating during the ride and by Motion Sickness Assessment Questionnaire before… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
125
3
12

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 137 publications
(156 citation statements)
references
References 31 publications
16
125
3
12
Order By: Relevance
“…However, from the pressure waveforms, we could reliably identify emetic events, with burst analysis showing approximately 6.5 retches/vomits per episode, which is similar to that recorded in other studies of either conscious (6.5 ± 0.2 retches/episode) or anesthetized (7.1 ± 0.7 retches/episode) Suncus murinus (Andrews et al, 1996; Huang et al, 2011). We also identified that respiratory rate increased by ~59%, with a concurrent 28% reduction in tidal volume (inspiratory time also reduced) during motion; increases in respiratory rate of the order of about 4–12% are also seen in humans experiencing nausea induced by a simulated roller coaster ride (Gavgani et al, 2016) and in dogs motion-induced emesis may also be accompanied by panting (Crampton, 1990). A recently published clinical study demonstrated that motion also induced an increase of respiratory rate, oxygen consumption and carbon dioxide production, and these effects were more prominent in highly-susceptible participants (Chen et al, 2016).…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…However, from the pressure waveforms, we could reliably identify emetic events, with burst analysis showing approximately 6.5 retches/vomits per episode, which is similar to that recorded in other studies of either conscious (6.5 ± 0.2 retches/episode) or anesthetized (7.1 ± 0.7 retches/episode) Suncus murinus (Andrews et al, 1996; Huang et al, 2011). We also identified that respiratory rate increased by ~59%, with a concurrent 28% reduction in tidal volume (inspiratory time also reduced) during motion; increases in respiratory rate of the order of about 4–12% are also seen in humans experiencing nausea induced by a simulated roller coaster ride (Gavgani et al, 2016) and in dogs motion-induced emesis may also be accompanied by panting (Crampton, 1990). A recently published clinical study demonstrated that motion also induced an increase of respiratory rate, oxygen consumption and carbon dioxide production, and these effects were more prominent in highly-susceptible participants (Chen et al, 2016).…”
Section: Discussionmentioning
confidence: 82%
“…These experiments were performed in animals implanted with radiotelemetry devices to permit recording of the gastric myoelectric activity (GMA) and body temperature, since alteration of gastric slow waves and hypothermia has been associated with motion-induced nausea in humans (Stern et al, 1987; Nalivaiko et al, 2015). We also recorded respiratory function, which is also disturbed during nausea and interrupted during emesis (Cowings et al, 1986; Himi et al, 2004; Gavgani et al, 2016; Horn et al, 2016). The collection of physiological data in Suncus murinus was also done in conjunction with an assessment of behavior to quantify side effects and to provide an insight into behaviors that collectively may be indicative of “nausea” (Horn et al, 2011, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Despite advancements in virtual reality (VR) technology, many people still report experiencing simulator sickness symptoms from its use (Rebenitsch and Owen, 2016;Gavgani et al, 2017;Duzmanska et al, 2018;Guna et al, 2019). Characterizing and quantifying these symptoms is challenging, as several factors are at play including a diverse range of technologies; the use of inconsistent terminology for sickness from using virtual environments; little consensus on the biological mechanisms of symptoms; the diverse range of VR content; along with user characteristics such as age and sex (Hale and Stanney, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Despite advancements in virtual reality (VR) technology, many people still report experiencing simulator sickness symptoms from its use (Dużmańska, Strojny, & Strojny, 2018;Gavgani, Nesbitt, Blackmore, & Nalivaiko, 2017;Guna et al, 2019;Rebenitsch & Owen, 2016).…”
Section: Introductionmentioning
confidence: 99%